ANALISIS STABILITAS LERENG MENGGUNAKAN SOFTWARE PLAXIS 8.6 DENGAN DINDING PENAHAN TANAH (RETAINING WALL) (STUDI KASUS RUAS JALAN NASIONAL BANDA ACEH-MEDAN STA 83+135 GUNUNG SEULAWAH) - Wihardi Wihardi; Munirwansyah Munirwansyah; Sofyan M. Saleh (Prodi Magister Teknik Sipil Unsyiah, 2018)
Road infrastructure is very important and is a key enabler for the economy. If the road infrastructure was damaged or had various problems such as sliding, the movement of goods and passengers will be hampered and delayed to the acceleration of development in the local area. The landslide and movement of groundwater is a problem that often occurs repeatedly on some streets. Therefore, it is necessary to study the strengthening of the slopes at the bottom of the road construction with retaining wall. This study aims to analyze slope stability by getting numbers Safety Factor (FK). The analysis is used to analyze the stability of slopesusing the finite element method with the help of software Plaids, The scope of this review includes the calculation of slope stability at the national road from Banda Aceh - Medan Sta. 83 + 185 Mount Selawah. The results of slope stability analysis on the existing condition by using Plaxis software at the point of a review is not safe (FK lower than 1.25). Thus, it is done handling the retaining wall, installation of anchors. Based on the analysis of slope stability after being given the strengthening of the slopes with a retaining wall and the installation of anchors using Plaxis software under the influence of traffic load in an unsafe condition (FK lower than 1.25). Then additional handling is done by changing the angle of the slope so that the value of the safety factor (FK) greater than 1.25.